Wagon-wheel irrigator for small gardens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A simple drip-irrigation system for small family vegetable gardens designed to use household waste water, has been developed in South Africa and could be used elsewhere. The system is set up like a wagon-wheel and at the centre, or hub, is a 200...